Answers

  • Brainly User
2014-09-14T22:40:00+05:30
Let denominator of the fraction be = d. Then numerator = d-4.                 Hence fraction = (d-4) / d. Now adding 1 to both numerator and denominator, fraction becomes [(d-4)+1] / (d+1) = (d-3) /(d+1) = 1/2          OR cross-multiplying, 2d - 6 = d+1 ==> 2d - d = 1+6 ==> d = 7.                  Therefore Denominator = 7 and numerator = 7-4 = 3. Hence fraction = 3/7
0
2014-09-15T03:58:08+05:30

Let denominator of the fraction be =x

ATQ

 Numerator = x-4.Then          

Fraction = (x-4) / x.

Adding 1 to both numerator and denominator, we get

[(x-4)+1] / (x+1) = (x-3) /(x+1) = 1/2

2x - 6 = x+1 [BY CROSS MULTIPLY]

2x - x = 1+6 ==> x=7

 Denominator = 7 and

Numerator = x-4 = 7-4=3 

HENCE THE FRACTION IS 3/7 

0